2019
DOI: 10.3390/nano9060869
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Nanophase Separation and Hydrophilic Morphology in Nafion and SPEEK Membranes: A Combined Experimental and Theoretical Studies

Abstract: The understanding of the relationship between the chemical structure and the hydrophilic structure is crucial for the designing of high-performance PEMs. Comparative studies in typical Nafion and sulfonated poly (ether ether ketone) (SPEEK) were performed using a combined experimental and theoretical method. SPEEK showed suppressed fuel crossover and good mechanical property but low water uptake, weak phase separation, and inadequate proton conductivity. Molecular dynamics (MD) simulation approaches were emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…If the IEC values are similar, the conductivity of the Nafion 212 is higher than that of the synthesized SPAES membranes. Fluorinated groups of Nafion have higher electronegativity than the hydrogen of hydrocarbon-based membranes; therefore, it is known that Nafion is more conductive than general hydrocarbon-based membranes [ 26 ]. Hex-SPAES-40 showed a higher conductivity value, even though it had a lower IEC value than Phe-SPAES-40.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the IEC values are similar, the conductivity of the Nafion 212 is higher than that of the synthesized SPAES membranes. Fluorinated groups of Nafion have higher electronegativity than the hydrogen of hydrocarbon-based membranes; therefore, it is known that Nafion is more conductive than general hydrocarbon-based membranes [ 26 ]. Hex-SPAES-40 showed a higher conductivity value, even though it had a lower IEC value than Phe-SPAES-40.…”
Section: Resultsmentioning
confidence: 99%
“…There are many research papers that consider the degree of hydrophilic–hydrophobic phase separation in TEM images with respect to ion conduction channels [ 16 , 26 ]. This is because when the moisture content of the polymer electrolyte membrane increases, adjacent hydrophilic clusters connect to each other to form ion-conducting channels that promote ion diffusion [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low membrane thickness (120-170 µm) and the solid electrolyte reduce the ohmic overpotential and allow the operation in a load-following mode with 100% turndown potential of the specific power input since the crossover rate is low and the response to power change is rapid [199]. Nafion, generally used as a membrane polymer due to its high stability, consist of a hydrophobic poly(tetrafluoroethylene) with a lateral branch of hydrophilic sulfonic acid functional group (-SO 3 H) [200]. Proton transport across the electrolyte is a combination of proton hopping (structural diffusion) among water molecules and diffusion in solution by forming a hydrated ion [201].…”
Section: Polymer Electrolyte Membrane Electrolysis Cellsmentioning
confidence: 99%
“…Even if Nafion ® is the most commonly used membrane, due to its high proton conductivity, some disadvantages, such as water uptake, methanol permeability and cost, have oriented research to the study of alternative polymers. Poly-ether-ether-ketone (PEEK) is a low cost thermoplastic, widely used in the space-flight, petroleum, chemical and medical industrial fields, due to its heat and corrosion resistant properties [3][4][5]. Moreover, a wide range of literature has shown that functionalized PEEK containing sulfonic groups is suitable for PEFC applications [6,7].…”
Section: Introductionmentioning
confidence: 99%